Competitive strategies, heterogeneous demand sources and firms' growth trajectories - Serenella Caravella; Francesco Crespi; Dario Guarascio; Matteo Tubiana (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
The present paper explores the demand-pull effect of distinct demand sources (i.e. households and retailers, other firms and public sector) on Italian companies' growth patterns. Data relies on the PEC (Indagine sulle Professioni e le Competenze) survey carried out by the Institute for Public Policy Analysis (INAPP), which provides a rich set of information on a representative sample of Italian companies (~32.000) observed during the years 2012, 2014 and 2017. In particular, we investigate if and to what extent firm-level growth profiles are linked to the prevalent source of the demand flows that such firms face. The analysis contextually accounts for the role played by technological and knowledge-related heterogeneities in shaping the growth pattern-demand type relationship. The empirical analysis shows that the demand-pull effect on firms' growth is heterogeneous across different types of demand sources and that the ability to seize the growth-related chances provided by distinct demand conditions is contingent on firms' specific knowledge profiles.
Keywords: L1; L21; L22; L25; 330; firms; growth; demand-pull; innovation